Web System for Data Collection and Data Transmission with MySQL Data Storage - Eka Aperinda Putri; Ulinnuha Latifa; Arnisa Stefanie (Journal of Information System, Informatics and Computing, 2022)
In the logistics service delivery industry, which is growing rapidly. In its operations, logistics service companies still use manual methods and recording on physical data. Therefore, an information system is needed to assist the process of data storage, monitoring, and reporting of goods data. With the creation of a web-based information system method, it will certainly make it easier for workers in logistics services to collect data on goods. From these problems, a web-based information system was created that can collect data on the number of incoming and outgoing goods, display graphs and also stock items for reporting, and user access rights management to distinguish different access rights in accessing the system. Making this web system is assisted by PHP and HTML languages, MySQL data storage, with interface design using Javascript and Bootstrap. It is proven very good in transmitting data with Quality of Service results with a delay calculation of 46.134 ms which shows a very good delay category with an index of 4; throughput calculation is 16132 kbps which shows the throughput category is good with index 3; and the calculation of packet loss is 0.00185528% which shows the packet loss category is very good with an index of 4. From these calculations it can be concluded that the Quality of Service produced by calculating the average index of 3.6 is very good.